Apunipima baby basket program: a retrospective cost study. Issue 1 (December 2016) - Edmunds, Kim; Searles, Andrew; Neville, Johanna; Ling, Rod; McCalman, Janya; Mein, Jacki
Abstract Background The Baby Basket initiative was developed by Apunipima Cape York Health Council (ACYHC) to address poor maternal and child health (MCH) in Cape York, the northernmost region of Queensland. While positive outcomes for Indigenous MCH programs are reported in the literature, few studies have a strong evidence base or employ a sound methodological approach to evaluation. The aim of the cost study is to identify the resources required to deliver the Baby Basket program in the remote communities of Cape York. It represents an initial step in the economic evaluation of the Apunipima Baby Basket program. The aim of this study was to report whether the current program represents an effective use of scarce resources. Method The cost study was conducted from the perspective of the health providers and reflects the direct resources required to deliver the Baby Basket program to 170 women across 11 communities represented by ACYHC. A flow diagram informed by interviews with ACYHC staff, administrative documents and survey feedback was used to map the program pathway and measure resource use. Monetary values, in 2013 Australian dollars, were applied to the resources used to deliver the Baby Basket program for one year. Results The total cost of delivering the Baby Basket progam to 170 participants in Cape York was 148, 642 or approximately, 874 per participant. The analysis allowed for the cost of providing the Baby Baskets to remote locations and the time for health workers to engage with women and thereby encourage a relationship with the health service. Routinely collected data showed improved engagement between expectant women and the health service during the life of the program. Conclusion The Apunipima Baby Basket cost study identifies the resources required to deliver this program in remote communities of Cape York and provides a framework that will support prospective data collection of more specific outcome data, for future cost-effectiveness analyses and cost-benefit analyses. An investment of 874 per Baby Basket participant was associated with improved engagement with the health service, an important factor in maternal and child health.